A study on personality traits influence the Bank Simpanan Nasional (BSN) employee’s job performance / Ahmad Izzat Hamzah and Siti Noor Aziefah Amira Mohd Nawi - Hamzah, Ahmad Izzat; Mohd Nawi, Siti Noor Aziefah Amira (Faculty of Business and Management, 2013)
This research title is Personality Traits Influence the Bank Simpanan Nasional (BSN) Employee’s Job Performance. This study has been conducted by many researchers in the past decades and in today’s era of globalization, personality of each of employees are important and must be measure by company to find the suitability for position and job task across many level in organization. The study will begin with the definition of personality along with the traits that associated with the personality. Many organizations have found that employee personality traits are important to their business. This is because based on past researchers finding, human resource managers can appoint their personals to appropriate jobs. The discussion will focuses on how personality traits impact employee’s job performance and to prove that personality traits can increase job performance for a long term period. To do this research, personality traits are based on big five model personality and it can be used as variables that contribute to the performance of the employee which are Neuroticism, Extraversion, Openness to Change, Conscientiousness and Agreeableness. As a big organization such as Bank Simpanan Nasional (BSN) which has thousand employees, they will face variety type of characteristic that can affect to job performance. Hence, the researcher chose employees at Bank Simpanan Nasional (BSN) as a respondent for this study because researcher currently doing internship at the organization and easy to get the feedback and see the view from inside of the company. Moreover the company is the headquarters for Bank Simpanan Nasional (BSN) around the country.